2021
DOI: 10.4251/wjgo.v13.i4.216
|View full text |Cite
|
Sign up to set email alerts
|

Latest therapeutic target for gastric cancer: Anthrax toxin receptor 1

Abstract: Anthrax toxin receptor 1 (ANTXR1), also known as tumor endothelial marker 8, is a highly conserved cell surface protein overexpressed in tumor-infiltrating vessels. It was first found in vascular endothelial cells of human colorectal cancer. Although our understanding of its physiological function is limited, it has been found that ANTXR1 binds collagen and promotes migration of endothelial cells in vitro . ANTXR1 is upregulated in vessels of different tumor types in mice and humans, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 28 publications
0
11
0
Order By: Relevance
“…ANTXR1 is a receptor for anthrax toxin and is highly expressed in tumor endothelial cells. It has been reported to be an oncogene and plays roles in tumor angiogenesis and in the growth, metastasis, and immunosuppression of many kinds of tumors (Huang et al, 2020;Sun et al, 2021). Its antibody-drug conjugate may facilitate selective destruction of tumor blood vessels yielding enhanced anti-cancer efficacy and reduced normal tissue toxicities (Frankel et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…ANTXR1 is a receptor for anthrax toxin and is highly expressed in tumor endothelial cells. It has been reported to be an oncogene and plays roles in tumor angiogenesis and in the growth, metastasis, and immunosuppression of many kinds of tumors (Huang et al, 2020;Sun et al, 2021). Its antibody-drug conjugate may facilitate selective destruction of tumor blood vessels yielding enhanced anti-cancer efficacy and reduced normal tissue toxicities (Frankel et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…The physiological roles of TEM8 and CMG2 are related to the regulation of extracellular matrix homeostasis and remodeling angiogenesis, cell migration, and cell spreading by interacting with the actin cytoskeleton, similar to integrins [ 5 , 61 , 70 ]. These functions may be related to tumor occurrence and metastasis [ 70 ]. Angiogenesis is regulated by interactions with components of the extracellular matrix (ECM).…”
Section: Ab Toxins That Utilize Proteins As Host Receptorsmentioning
confidence: 99%
“…Studies have demonstrated that TEM8/ANTXR1 is enriched in triple negative breast cancer (Xu et al, 2021), prostate cancer (Li et al, 2021a), gastric cancer (Li et al, 2021b;Sun et al, 2021), pancreatic cancer (Alcalá et al, 2019), angiosarcoma (Kusaba et al, 2021(Kusaba et al, ), colon cancer (Ł et al, 2021, and non-small cell lung cancer (NSCLC) (Gong et al, 2021). In multiple tumor types, upregulation of TEM8/ ANTXR1 is a negative prognostic indicator (Li et al, 2021a;Ł et al, 2021;Ding et al, 2021).…”
Section: Study Description Outcomesmentioning
confidence: 99%
“…However, understanding SVV-001 and the unique tumor microenvironment, represented by upregulation of TEM8/ANTXR1, that it targets, has the potential to provide additional clues about mechanisms of resistance to immunotherapy and chemotherapy in neuroendocrine neoplasms and other cancers. TEM8/ANTXR1 upregulation has been described in a variety of solid tumors types including triple negative breast cancer (Xu et al, 2021), prostate cancer (Li et al, 2021a), gastric cancer (Li et al, 2021b;Sun et al, 2021), pancreatic cancer (Alcalá et al, 2019), angiosarcoma (Kusaba et al, 2021(Kusaba et al, ), colon cancer (Ł et al, 2021, and NSCLC (Gong et al, 2021). Lineage plasticity with a transformation from adenocarcinomas to carcinomas with neuroendocrine differentiation has been described in a variety of solid tumors, including lung and prostate primary tumors (Farrell et al, 2017;Rubin et al, 2020;Ito et al, 2021).…”
Section: Seneca Valley Virus In Well Differentiated Neuroendocrine Tu...mentioning
confidence: 99%